Lincoln Gordon : Architect of Cold War Foreign Policy - Smith, Bruce L. R. (Book collections on Project MUSE., 2015)
After World War II, American statesman and scholar Lincoln Gordon emerged as one of the key players in the reconstruction of Europe. In this biography, Bruce L.R. Smith examines Gordon's substantial contributions to US mobilization during the Second World War, Europe's postwar economic recovery, the security framework for the North Atlantic Treaty Organization, and US policy in Latin America.